Impact of Reservoir Horizontal Permeability Vertical Distribution on Recovery Efficiency Based on Deepwater Massive Sands - Azman Munthoha Maula; Tsani Sabila; Putri Agustryani; Friska Hasugian; Dwi Miftha Kurnia; Randy Yusuf Kurniawan; Rozi Afdi (Journal of Petroleum and Geothermal Technology, 2026)
The influence of Deep-Water Massive Sands (DWMS) internal architecture on hydrocarbon recovery remains an area of ambiguity. This research endeavor aimed to elucidate the bed-scale ramifications of the vertical distribution of horizontal permeability, as determined from documented DWMS outcrop sedimentological analyses, on hydrocarbon recovery and sweep efficiency. This was achieved through the application of numerical waterflood simulations. Model construction leveraged outcrop textural parameters, including grain size, sorting, and orientation, in conjunction with analogous turbidite petrophysical subsurface data. The observed outcomes from four simulated heterogeneous cases revealed distinct trends in recovery efficiency, with variations up to 10%. These trends were attributable to the efficiency of water sweep and the interactive effects of vertical permeability heterogeneity, gravitational forces, and viscous forces. Specifically, the most stable, piston-like water sweep efficiency was associated with coarsening-upward permeability trends, followed by intermediate sweep efficiencies in anomalous and ungraded DWMS trends, and finally, the most unstable sweep efficiency in idealized trends.